Video games and the mind essays on cognition, affect and emotion - Perron, Bernard 1965-; Schröter, Felix 1985- (McFarland & Company, Inc., Publishers, 2016)
"With psychological theories of cognition, affect and emotion as a reference point, this collection of new essays offers various perspectives on how players think and feel about video games and how game design and analysis can build on these processes"--
Keywords: Video games / Psychological aspects; Video games / Design; Psychologie; Gefühl; Kognition; Videospiel; Aufsatzsammlung